0.5 has been ranked among the top 0.5% of scientists worldwide, according to the most recent 2024 ScholarGPS rankings. - Hadjimitsis, Diofantos G. (My University, 2026)
https://www.cna.org.cy/en/article/8559031/cut-professor-diofantos-hadjimitsis-among-top-0-5-scientists-worldwide
Keywords: Worlds Top Scientists